2016
DOI: 10.1080/01676830.2016.1176210
|View full text |Cite
|
Sign up to set email alerts
|

Orbital exenteration: The 10-year Massachusetts Eye and Ear Infirmary experience

Abstract: The authors report their experience with orbital exenteration surgery at one academic institution over a 10-year period and review the literature. This retrospective cohort study monitored outcomes of all patients who underwent orbital exenteration surgery at Massachusetts Eye and Ear Infirmary between January 2003 and January 2013. Patients with no follow-up data or survival data were excluded from the study. The main outcome measures were surgical complications, disease status of surgical margins, need for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
3
24
1
Order By: Relevance
“…In our study, positive surgical margins were associated with a shorter OS according to the log-rank test ( p = 0.002). These results are consistent with those published by Gerring et al [ 13 ], although other authors have not been able to show any OS improvement despite the presence of clear surgical margins [ 4 , 7 , 12 , 28 ]. Another important factor known to affect OS is the presence of synchronous micro-metastases that are suspected to be already present at the time of orbital exenteration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, positive surgical margins were associated with a shorter OS according to the log-rank test ( p = 0.002). These results are consistent with those published by Gerring et al [ 13 ], although other authors have not been able to show any OS improvement despite the presence of clear surgical margins [ 4 , 7 , 12 , 28 ]. Another important factor known to affect OS is the presence of synchronous micro-metastases that are suspected to be already present at the time of orbital exenteration.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with previous studies. In the current literature, the 1-year OS ranges between 50.5% [ 24 ] and 97% [ 2 ] and the 5-year OS ranges between 37% [ 7 ] and 92% [ 8 ]. Kuo et al have reported a 5-year OS of 92% and they have advocated the need for prompt and aggressive surgical treatment [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rahman et al [9] reported that 64 of their 69 cases required exenteration for malignant disease. Other authors have published similar results in their studies: for example, Nagendran et al [8] found 23 of 25 exenterations were for malignancies. Also, in the studies of Bartley et al [7] (n = 100 / 102), Levin and Dutton [11] (n = 93 / 99), and Mohr and Esser [10] (n = 74 / 77), similar results were found.…”
Section: Discussionsupporting
confidence: 60%
“…The mean age of our patients was 55.43 ± 27 years. The mean age of patients undergoing orbital exenteration is commonly older than 50 years [81115].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation